Management of Congenital Nasolacrimal Duct Obstruction with Probing, Experience in a Mexican Eye Center - Zuazo, Francisca; Morales, Osiris Olvera; Canales, José L. Tovilla; Castañeda, Ángel Nava (Nepalese Journal of Ophthalmology, 2019)
Objective: To describe the management, complications and prognosis of lacrimalprobing in patients with congenital nasolacrimal duct obstruction (CNLDO).Materials and Methods: Retrospective, observational and analytical study. We studied the prevalence, symptoms and signs, both before and after probing, in patients with CNLDO diagnosed between 2010 and 2017 at Instituto Fundación Conde deValenciana.Results: The prevalence at our hospital of congenital nasolacrimal duct obstruction in children less than 1 year of age was 16.1%. 71 eyes of 56 patients undergoing probing were analyzed. 61% of patients were male. The right eye was affected in 46.4%.The average age of diagnosis of CNLDO was 10.2±7.6 months. 84.5% consulted for excessive tearing and 73.2% because of eye discharge. On ophthalmological examination, 71.8% had increased tear meniscus and 45.1% had discharge from punctum when digital pressure was applied to the lacrimal sac. The average age at the time of probing was 14.1±8.4 months. Subsequent to the probing, only 21.1% reported presence of tearing and 5.6% reported ocular discharge, both with a statistically significant reduction (p